2010
DOI: 10.1109/tasc.2009.2039136
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Growth Rate of a YBCO Bulk in the Melt-Textured Process Under 1 atm Oxygen Pressure

Abstract: By the employment of 1 atm oxygen pressure as the growth atmosphere, we report a success in the enhanced growth rate of the melt-textured (MT) YBCO bulk. A well-oriented c-axis single-domain bulk with a size of 42 mm in diameter was fully grown at a high average growth rate of about 0.32 mm/h, which is 1.5 times larger than that in air. It was found that the increased oxygen partial pressure has a profound influence on the MT growth (MTG) for YBCO. The enhanced growth rate can be interpreted by both increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The results are in agreement with the interpretation developed earlier that the range of RE/Ba substitution in GdBCO is smaller than in other (LRE)BCO, such as SmBCO and NdBCO materials, as the Gd 3+ ion is smaller than Sm 3+ or Nd 3+ ions 13 . On the other hand, it has been reported that the average growth rate of MT in a pure oxygen environment can be enhanced by >0.5 times for YBCO, which can be explained by the increase of both the solubility and the diffusion coefficient of yttrium in a Ba–Cu–O liquid under a high oxygen partial pressure 25 . It can be deduced further that the growth rate of GdBCO bulks can be increased in pure oxygen in comparison with that in air.…”
Section: Study Of the Superconducting Properties Of Gdbco Singlementioning
confidence: 99%
“…The results are in agreement with the interpretation developed earlier that the range of RE/Ba substitution in GdBCO is smaller than in other (LRE)BCO, such as SmBCO and NdBCO materials, as the Gd 3+ ion is smaller than Sm 3+ or Nd 3+ ions 13 . On the other hand, it has been reported that the average growth rate of MT in a pure oxygen environment can be enhanced by >0.5 times for YBCO, which can be explained by the increase of both the solubility and the diffusion coefficient of yttrium in a Ba–Cu–O liquid under a high oxygen partial pressure 25 . It can be deduced further that the growth rate of GdBCO bulks can be increased in pure oxygen in comparison with that in air.…”
Section: Study Of the Superconducting Properties Of Gdbco Singlementioning
confidence: 99%
“…Furthermore, the oxygen controlled melt growth process is generally utilized to suppress the RE/Ba substitute in LREBCO 7Ày (LRE = Gd, Sm, Nd) system, which deteriorates the superconducting property [70]. In addition, the growth rate of REBCO bulks in an elevated oxygen pressure is higher than that in air [71]. With respect to the thermal stability of REBCO system, the oxygen affects the solubility of RE elements in the liquid and the t.c.s.…”
Section: Temperature Coefficient Of Solubilitymentioning
confidence: 99%
“…T ARGETING practical applications of High-Temperature Superconducting (HTS) bulks [1]- [3], a great deal of effort has been carried out regarding the art of growing materials, their properties and their modelling [4]- [7]. With regards to the latter, analytical formulae, in the simplest 2D cases using the Bean's Critical State Model (BCSM), and numerical models, in the most complex geometries involving 3D modelling techniques and/or more refined critical current dependencies, have been developed to predict the magnitude of the penetration field and the feasibility of trapping large magnetic fluxes [8]- [10].…”
Section: Introductionmentioning
confidence: 99%